OCCURRENCE OF STOMATITIS IN THE MOUTH AND ITS TREATMENT (Spectrum Journal of Innovation, Reforms and Development, 2023)
Pathological changes in the physical-biochemical state of boys with traumatic stomatitis a comprehensive study of pathological changes identified among boys at the same time as the definition of a common somatic disease in the case of patients with other expressed shifts among boys in the course of these diseases expressed among boys clinpatological shifts in the case when a garden.